Development of Augmented Reality Learning Media Based on Assemblr Edu to Improve Students' Creativity Abilities - Sari, Naila Nurhana; Sari, Prima Mutia (Universitas Pendidikan Mandalika, 2025)
The purpose of this study is to design digital learning media that utilize Augmented Reality (AR) technology through the Assemblr Edu platform on the topic of Earth’s Rotation and Revolution to enhance students’ creativity. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of five main stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews and questionnaires administered to subject matter experts, media experts, teachers, and students. Both qualitative and quantitative techniques were used for data analysis. The validation results showed that the developed learning media achieved a feasibility score of 86% from material experts and 95% from media experts, both of which are categorized as very feasible. Meanwhile, responses from teachers and students obtained scores of 95% and 84%, respectively, classified as very good. Overall, these findings indicate that Assemblr Edu–based AR learning media are suitable for use in science learning and have strong potential to enhance students’ creativity and understanding of abstract concepts.